2010
DOI: 10.1016/j.trstmh.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of insulin-like growth factor 1, insulin-like growth factor binding protein 3 and bone mineral density in patients with chronic hepatitis C virus in Cairo, Egypt

Abstract: Insulin-like growth factor 1 (IGF-1) levels have been found to correlate with measurements of bone mineral density (BMD) in liver diseases. This study investigated the relationship between IGF-1, insulin-like growth factor binding protein 3 (IGFBP-3) and BMD in patients with chronic hepatitis C virus. This study was conducted for 30 patients with chronic hepatitis C virus infection (16 patients without and 14 patients with cirrhosis) and 11 healthy controls. Serum levels of IGF-1 and IGFBP-3 and BMD of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…In our studies, examination of serum IGF-1 concentration confirmed previous reports which observed lower concentrations in CH-C or in HCV-related liver cirrhosis, as compared to the control (25,26,29,31,32,48). Patients with chronic HCV infection manifested GH insufficiency and persistent GH resistance of hepatocytes, which may also promote a decrease in liver production of IGF-1 (48).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our studies, examination of serum IGF-1 concentration confirmed previous reports which observed lower concentrations in CH-C or in HCV-related liver cirrhosis, as compared to the control (25,26,29,31,32,48). Patients with chronic HCV infection manifested GH insufficiency and persistent GH resistance of hepatocytes, which may also promote a decrease in liver production of IGF-1 (48).…”
Section: Discussionsupporting
confidence: 90%
“…Other studies on the significance of this component of IGF axis in chronic hepatitis were focused mainly on alcohol-or HBV-related liver injuries (28,47). Although the lowered concentration of IGFBP-3 was also documented in patients with CH-C, as compared to the control (30,31), no correlation was detected with the clinicopathological data (grading, staging, transaminase levels) (30) or negative correlations were demonstrated with age and AST activity, and positive correlations with serum albumin and prothrombin concentration (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these phenomena were accompanied by increased daily secretion of GH in the study group (88.3 ng/mL vs. 48.04 ng/mL, p < 0.001). This trend has been observed by different authors [33,46,47]. We noted a positive correlation linking BMD and IGF-I and IGFBP-3.…”
Section: Prace Oryginalnesupporting
confidence: 90%